Overview of web mining and its applications 2 - Mobasher, Bamshad (Henry Stewart Talks, 2008)
Web usage mining for e-business analytics, Typical sources of data and user transactions, A typical server log, Usage data preparation tasks, Levels of aggregation in web usage analysis, Conceptual representation of user transactions, Web usage mining as a process, Common tasks, Association analysis for e-commerce, Association rules, Characterizing user segments via clustering, Clustering user transactions, Collaborative filtering, Web personalization
Archived at 2022/03/17